Association between HLA Antigens and Birch Pollen Allergy in Japanese Subjects - Kumai, Megumi; Miyokawa, Naoyuki; Adachi, Toshihide; Katagiri, Makoto; Unno, Tokuji (American journal of rhinology, 1990)
Birch pollen is a very common cause of nasal allergy (pollinosis) not only in Scandinavia, Europe, Canada, and the northern part of the United States but also in Hokkaido, Japan. Although there are many papers describing the association of HLA antigens and pollinosis caused by many other allergens, there is no report about the association of HLA antigens and birch pollen allergy. In this paper, we performed an HLA population study of birch pollen-allergic patients in Japan and their pattern analysis of HLA-DRB and HLA-DQB gene by the Southern blot hybridization technique. Our population study data indicated that the HLA-DR9 and HLA-DQw3 phenotypes strongly associated with the development of birch pollen allergy in Japanese subjects. By restriction fragment length polymorphism pattern analysis, some restriction fragments of the HLA-DQB gene were detected only in the patient group. These data suggested that there was a significant association between HLA class II antigens and the development of birch pollen allergy in Japanese subjects.